A Contribution to the History of Repentance Prayers in the Slavic South during the 15th Century - Tsibranska-Kostova, Mariyana (Studia Ceranea, 2023)
The article explores and offers a diplomatic edition of A Very Useful Confession for Unction for Every Christian, for the Black and White Clergy. This is an autograph by Vladislav the Grammarian placed in the Trebnik of Monk David (1480s), manuscript 1/42 in the collection of the Rila Monastery. The analysis is based on the working hypothesis that after the conquest of Constantinople by the Ottoman Turks in 1453, the Ottoman invasion of the Balkans was perceived as a God’s punishment for the sins of the Orthodox Christians. This idea became strongly present in a number of texts. Penitential prayer patterns multiply in the literature. The Greek prototype of the text under study has not been identified yet, but features a close relation to the prayers with the so-called accumulation of sins. It is, in essence, a confession which is performed in connection with the sacrament of the eleosvet (anointing of the sick) before receiving communion and the anointing with holy oil. The textual unit was purposefully introduced into Monk David’s Trebnik and reflected topical textual additions to the basic composition of the Slavonic Trebnik.